Intervention and mediation effects of a community-based singing group on older adults’ perceived physical and mental health: the Sing4Health randomized controlled trial - Galinha, Iolanda Costa (2021)
Objective To examine short- and long-term effects of a group singing program on older adults' perceived physical and mental health levels, and also investigate subjective well-being (life satisfaction, positive/negative affect and hedonic balance), body balance and serum biomarkers (C-reactive protein and erythrocyte sedimentation rate) as putative mediating mechanisms, controlling for the cognitive status of the participants. Design: The randomized controlled trial included 149 participants (60 to 95 years), allocated to an immediate intervention group (IG) or a wait-list active control group (WLG). The intervention comprised 34 sessions of group singing during 4-months. Main outcome measures: Self-report measures of physical health, anxiety, stress, and depression. Blinded assessments were conducted at baseline, post-intervention (4 months) and follow-up (6 months). Results: Participants in the IG reported a lower decline in perceived physical health after the intervention, as compared to the WLG. These benefits were maintained at follow-up. Singing-related changes in physical and mental health outcomes were mediated via an increase in positive affect. Moderation results showed that participants with very low cognitive functioning reported more anxiety and depression symptoms after the intervention. Conclusions: These findings provide further understanding on the psychological and physical mechanisms and effects of group singing in older adults.